STRENGTHENING THE PERSONAL AND PROFESSIONAL INTEGRATION OF STUDENTS: THE PATH TO HOLISTIC DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article explores the concept of strengthening the personal and professional integration of students and its importance in promoting holistic development. Since universities seek to train students as competitive and quality personnel of the modern world, attention should be paid not only to acquiring knowledge and skills, but also to combining personal values, beliefs and identity with their professional aspirations. This article examines the benefits of personal and professional integration, including increased productivity, increased job satisfaction, improved well-being, and more professional success. It also discusses strategies and practices that can be implemented in higher education institutions to promote personal and professional integration. By developing a sense of consistency and coherence between personal and professional identity, students can move towards holistic growth, self-awareness and meaningful contribution to the development of society.